AYUSHMAN BHARAT-Flagship Healthcare Programme by Government of India- A CRITICAL3600 REVIEW - Prakash, N.S.; Raghavendra (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Government of India has initiated a mega community health scheme under the banner ‘Ayushman Bharat’ (AB) which is arguably a biggest scheme in the world with steep increase in medical cover for economically vulnerable section from Sep 2018. This aims to provide secondary and tertiary care to approximately 40% of the population who are in the lower economic strata. This community health insurance scheme is on the lines of earlier similar schemes of Central and several State Governments but much wider in terms of cover. Objectives: The scheme being very ambitious, this paper attempts to do programme evaluation and understand whether the overall objective is met in terms of covering the most needed requirements of poor people in all respects. Given the Vision of ‘Health for All’ within the defined group of people, how well the challenges are addressed is explored. Methods: A very exhaustive survey of all literatures and published data including the information on the official web site of AB is made and compared with earlier schemes and similar schemes across other parts of globe. Results: The scheme has been fairly successful in terms of providing treatment to vast majority of people, who otherwise cannot afford major treatments. There is a strong need to scale up the infrastructure and increase coverage. Conclusions: With the larger objective of ‘Universal Health’, the beneficiaries list need to be reviewed as the current list nine years old. The scheme should provide more emphasis on preventive care and look at bringing down the out of pocket expenses.